The Role of Surgery in Locally Advanced Cervical Cancer - -, Nasdaldy (Indonesian Journal of Cancer, 2008)
The Role of Surgery in Locally Advanced Cervical CancerÂ full text: http://www.scribd.com/doc/45153183/The-Role-of-Surgery-in-Locally-Advanced-Cervical-Cancer